Existing capacity to manage pharmaceuticals and related commodities in East Africa: an assessment with specific reference to antiretroviral therapy - Anokbonggo Willy W; Ogwal-okeng Jasper; Tumwikirize Winnie; Owino Erisa; Obua Celestino; Odoi-adome Richard; Waako Paul J; Matowe Lloyd; Aupont Onesky (BMC, 2009)
Abstract Background East African countries have in the recent past experienced a tremendous increase in the volume of antiretroviral drugs. Capacity to manage these medicines in the region remains limited. Makerere University, with technical assistance from the USAID supported Rational Pharmaceutical Management Plus (RPM Plus) Program of Management Sciences for Health (MSH) established a network of academic institutions to build capacity for pharmaceutical management in the East African region. The initiative includes institutions from Uganda, Tanzania, Kenya and Rwanda and aims to improve access to safe, effective and quality-assured medicines for the treatment of HIV/AIDS, TB and Malaria through spearheading in-country capacity. The initiative conducted a regional assessment to determine the existing capacity for the management of antiretroviral drugs and related commodities. Methods Heads and implementing workers of fifty HIV/AIDS programs and institutions accredited to offer antiretroviral services in Uganda, Kenya, Tanzania and Rwanda were key informants in face-to-face interviews guided by structured questionnaires. The assessment explored categories of health workers involved in the management of ARVs, their knowledge and practices in selection, quantification, distribution and use of ARVs, nature of existing training programs, training preferences and resources for capacity building. Results Inadequate human resource capacity including, inability to select, quantify and distribute ARVs and related commodities, and irrational prescribing and dispensing were some of the problems identified. A competence gap existed in all the four countries with a variety of healthcare professionals involved in the supply and distribution of ARVs. Training opportunities and resources for capacity development were limited particularly for workers in remote facilities. On-the-job training and short courses were the preferred modes of training. Conclusion There is inadequate capacity for managing medicines and related commodities in East Africa. There is an urgent need for training in aspects of pharmaceutical management to different categories of health workers. Skills building activities that do not take healthcare workers from their places of work are preferred.